Why fish don't exist ebook A story of loss, love, and the hidden order of life. - Miller, Lulu (2020)
A Best Book of 2020: The Washington Post * NPR * Chicago Tribune * Smithsonian A "remarkable" ( Los Angeles Times ), "seductive" ( The Wall Street Journal ) debut from the new cohost of Radiolab , Why Fish Don't Exist is a dark and astonishing tale of love, chaos, scientific obsession, and—possibly—even murder.​ "At one point, Miller dives into the ocean into a school of fish...comes up for air, and realizes she's in love. That's how I felt: Her book took me to strange depths I never imagined, and I was smitten." — The New York Times Book Review David Starr Jordan was a taxonomist, a man possessed with bringing order to the natural world. In time, he would be credited with discovering nearly a fifth of the fish known to humans in his day. But the more of the hidden blueprint of life he uncovered, the harder the universe seemed to try to thwart him. His specimen collections were demolished by lightning, by fire, and eventually by the 1906 San Francisco earthquake—which sent more than a thousand discoveries, housed in fragile glass jars, plummeting to the floor. In an instant, his life's work was shattered. Many might have given up, given in to despair. But Jordan? He surveyed the wreckage at his feet, found the first fish that he recognized, and confidently began to rebuild his collection. And this time, he introduced one clever innovation that he believed would at last protect his work against the chaos of the world. When NPR reporter Lulu Miller first heard this anecdote in passing, she took Jordan for a fool—a cautionary tale in hubris, or denial. But as her own life slowly unraveled, she began to wonder about him. Perhaps instead he was a model for how to go on when all seemed lost. What she would unearth about his life would transform her understanding of history, morality, and the world beneath her feet. Part biography, part memoir, part scientific adventure, Why Fish Don't Exist is a wondrous fable about how to persevere in a world where chaos will always prevail.